TINGKAT KEPUASAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TEMPE OLEH KONSUMEN RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Rizky Eko Prasetyo; Wuryaningsih Dwi Sayekti; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to investigate attributes of tempeh desired by consumer households, consumers satisfaction levels on tempeh, the pattern of tempeh demand, and factors affecting tempeh demand in Bandar Lampung City. This study is conducted in Bandar Lampung City. Data is collected in December 2016 to February 2017. The population in this study is household in Bandar Lampung City. The samples employed in this study are 75 households chosen by multistage random sampling method. The results showed that tempeh attributes  wanted by consumer households were cheap price, good taste, unique looks, good packaging, hygienic tempeh, quality standard, containing good nutrients, and accesibility location to purchase tempeh. Consumer households in Bandar Lampung City were satisfied by tempeh products. Tempeh demand patterns by consumer households in Bandar Lampung City were as follows: the average of tempeh purchases by household was 1,600 grams per week and the average of purchase frequency was 1.72 times per week. The total of tempeh consumption was 66.67 percent processed by frying, mostly be purchased at the market. Affecting factors on tempeh demand were price of tempeh, vegetable oil, wheat flour, and eggs.Key words: demand, consumer satisfaction, tempeh